Modification of the Patient Competency Rating Scale to Measure Anosodiaphoria after Severe Acquired Brain Injury: Preliminary Findings. (22nd December 2021) - Bivona, U; Costa, A; Ciurli, P; Donvito, T; Lombardi, G; Misici, I; Moretti, G; Caltagirone, C; Formisano, R; Prigatano, G P
Abstract: Objective: Impaired self-awareness (ISA) of altered functional capacities is a common sequelae of severe acquired brain injury that can severely hamper neuro-rehabilitation in this clinical population. ISA is frequently associated with anosodiaphoria and/or apathy. Although several scales are available to measure apathy, no tools have been published to specifically assess anosodiaphoria after acquired brain injury. In this paper, we reported an initial effort to develop an anosodiaphoria subscale in a commonly used measure of ISA, that is, the Patient Competency Rating scale-neurorehabilitation form (PCRS-NR). Method: A sample of 46 participants with severe acquired brain injury completed a functional, ISA, apathy, and anosodiaphoria assessment. One informal caregiver of each patient participated in the study. Thus, we were able to obtain external data on his/her level of functional competencies, and self-awareness, which allowed separating patients with low self-awareness (LSA) from those with high self-awareness (HSA). Finally, the patients were compared with 44 healthy age–gender–years of formal education matched control participants (HCs). Results: Compared to both patients with HSA and HCs, patients with LSA demonstrated greater anosodiapvhoria and lower levels of functioning than both HSA patients and HCs. A stronger relationship emerged between ISA and anosodiaphoria rather than with apathy. Conclusions: These initial findings provide support that PCRS scale can be adapted to measure anosodiaphoria as well as ISA. The findings reveal a stronger correlation between this measure of anosodiaphoria and ISA compared with the correlation of apathy to ISA. The present method for measuring anosodiaphoria takes into account the actual levels of patients' functioning.